Production and compositional studies of milk in local Pabna cows of Bangladesh (Asian Journal of Medical and Biological Research, 2019)
The Pabna is one of the potential local cattle breeds in Bangladesh regarding milk production and its nutritive quality. The aim of the study was to know the effect of lactation length, parity and management on production performance and nutritional/physiochemical composition of the milk of local Pabna cows. Besides the regular milking, 15 days’ interval test day milking was recorded from 12 local Pabna cows with different lactation period (up to fifth month of calving) from BLRI Regional Station, Baghabari during January-September, 2018. In addition, 12 and 16 milk samples (200 ml/sample) were collected from the cows raised at BLRI Regional Station and the community of Dairy Development Research Project at Bera, Pabna district during June, 2018, respectively. Data were analyzed in an ANOVA of Completely Randomized Design and independent sample t-test, respectively, using SAS version 9.1.3 (SAS Institute Inc., Cary, NC, USA) including Tukey’s HSD post hoc test to separate means. The average daily milk yield was significantly (p